The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/09599916.2016.1258718
|View full text |Cite
|
Sign up to set email alerts
|

A robust house price index using sparse and frugal data

Abstract: In this article, we describe a house price index algorithm which requires only sparse and frugal data, namely house location, date of sale and sale price, as input data. We aim to show that our algorithm is as effective for predicting price changes as more complex models which require detailed or extensive data. Although various methods are employed for determining house price indexes, such as hedonic regression, mix-adjusted median or repeat sales, there is no consensus on how to determine the robustness of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(45 citation statements)
references
References 47 publications
(61 reference statements)
0
45
0
Order By: Relevance
“…Many researchers have struggled with the term “average.” Although the statistical mean or median might seem to be the most representative average, the statistical mean or median no longer stands as a representative standard when there is only limited information and/or the data is skewed. According to information theory, “representativeness” converges to the exemplar that holds the most meaningful information ( Maguire et al, 2016 ). For example, researchers who construct house price indices can sometimes find that their “average” house price is, in fact, less than both the statistical mean price and the median house price.…”
Section: Major Theoretical Accountsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have struggled with the term “average.” Although the statistical mean or median might seem to be the most representative average, the statistical mean or median no longer stands as a representative standard when there is only limited information and/or the data is skewed. According to information theory, “representativeness” converges to the exemplar that holds the most meaningful information ( Maguire et al, 2016 ). For example, researchers who construct house price indices can sometimes find that their “average” house price is, in fact, less than both the statistical mean price and the median house price.…”
Section: Major Theoretical Accountsmentioning
confidence: 99%
“…In this scenario, people may see the comparison target ( the average person ) not as the statistical mean or median but as someone with below-median ability or in other words, mediocre ability. We believe that when trying to conjure up an average, people choose a target they believe is the most representative of the group, and this comparison target is more often than not someone with below-median ability ( Maguire et al, 2016 ), particularly in the traditionally measured ability domains in the BAE literature. In other words, the BAE may not be an accurate reflection of self-enhancement bias, if people perceive “average” not as a neutral statistical term but as a slightly negative term connoting mediocrity, found somewhere below median.…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulated within this is the key question concerning how to control by quality given the different nature of the commodity (housing) and the quantity consumed. However, beyond this initial point of agreement there is an apparent lack of consensus on how an index should be constructed though three main methods to build house prices indices are frequently reported in the literature (Rapport, 2008;Coulson, 2012;Goh et al, 2012;P. Maguire, Miller, Moser, & R. Maguire, 2016).…”
Section: House Price Indices Constructionmentioning
confidence: 99%
“…Third, that houses which resale frequently tend to appreciate at higher rates. Fourth, that short holding periods may capture significant improvement to properties thereby violating assumptions on constant quality (Maguire et al, 2016;Bollerslev et al, 2016;Goh et al, 2012). Indeed, Goh et al (2012) identified that of five different models/variations they assessed, the repeat sales model was the least preferred.…”
Section: House Price Indices Constructionmentioning
confidence: 99%
“…Always, we are led back to the idea that the ultimate measurement is one that reflects the aggregation of a large number of independent samples (see Ref. 7). Independence is the cornerstone of measurement, not truth, nor the eradication of uncertainty.…”
Section: The Link Between Statistical Uncertainty and Stabilitymentioning
confidence: 99%